The Performance Of Madrasah Principals As Supervisors In Fostering Teacher Professionalism At Islamic Educational Institutions - Qodiriyah; Samsul Arifin; Saihan (Indonesian Journal of Educational Science (IJES), 2026)
This study aims to examine the performance of madrasa principals as supervisors in fostering teacher professionalism in Islamic educational institutions through a multi-case study at MA Nurul Islam Bades and MA Syarifuddin Lumajang. A qualitative approach with a multi-case design was employed to explore the processes of planning, implementation, and follow-up of academic supervision. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using an interactive model involving data reduction, display, and conclusion drawing. The findings reveal that the two madrasas demonstrate both convergent and divergent supervisory practices. In the planning and implementation stages, MA Syarifuddin Lumajang adopts a more structured and formal approach based on measurable performance indicators, while MA Nurul Islam Bades applies a flexible and context-responsive approach grounded in teachers’ practical needs. Both institutions employ humanistic and collaborative supervision; however, MA Nurul Islam emphasizes a familial-cultural approach, whereas MA Syarifuddin integrates professional and procedural systems. In terms of follow-up supervision, MA Nurul Islam prioritizes personal mentoring, dialogic feedback, and spiritually grounded guidance, while MA Syarifuddin develops systematic programs, including training, formal evaluations, and structured professional learning communities. These findings indicate that teacher professionalism is enhanced through the integration of personal, systemic, and spiritual dimensions. Therefore, this study proposes an integrative supervision model that is adaptive, collaborative, and value-based as an effective strategy to improve teacher professionalism in Islamic educational contexts.